(untitled) (Research, Society and Development, 2020)
In this article we present the results of an investigation that sought to characterize the relationships of learners with knowledge and learning activities, with the school and other environments as means where learning occurs. The subjects of the study were middle school students, in Paraná, Brazil. The methodological procedures were based on the content analysis of apprentices reports about their routines for studying school content. The characterization of relationships and learning activities consisted of categorizing relationships according to the perspective of learning venues, and in categories emerging from the analysis. Based on these procedures, we identified that the learning activities were of the presential school types, and complementary presential and virtual, performed about the more, and less free forms of circulation of knowledge. The relationships between apprentices and knowledge were epistemic (related to understanding), personal (to likings) and social (to values); and involved the formal learning venue, different types of environments, and school situations, family and use of digital platforms. Among these relationships, we highlight the likings and values attributed by apprentices to carrying out certain learning activities with the most free forms of circulation of knowledge. For example, the manipulation of real objects, interaction with sensory impressions, and expression of doubts about the contents school. We believe that the results presented here may be useful in discussions about teaching and learning, teacher training, and learning with familiar practices and use of digital technologies.